2022
DOI: 10.3390/jcm11071976
|View full text |Cite|
|
Sign up to set email alerts
|

The Fate of Antibiotic Impregnated Cement Space in Treatment for Forefoot Osteomyelitis

Abstract: Forefoot osteomyelitis can be an extremely challenging problem in orthopedic surgery. Unlike conventional methods, such as amputations, antibiotic impregnated cement space (ACS) was recently introduced and perceived as a substitute for amputation. The purpose of this study was to compare clinical features between diabetic and non-diabetic groups and to evaluate the efficacy of ACS in the treatment of forefoot osteomyelitis, by identifying the clinical characteristics of ACS. We inserted ACS into the forefoot o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Yalikun et al showed that 88% of reinfections occurred at the docking site 47 . Second, the local antibiotics in the cement spacer can achieve a concentration far above the minimal inhibitory concentration to eradicate residual pathogens after debridement 37,48,49 . Additionally, the staged surgical process guaranteed a high cure rate, especially in patients with poor soft-tissue condition and active infections 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Yalikun et al showed that 88% of reinfections occurred at the docking site 47 . Second, the local antibiotics in the cement spacer can achieve a concentration far above the minimal inhibitory concentration to eradicate residual pathogens after debridement 37,48,49 . Additionally, the staged surgical process guaranteed a high cure rate, especially in patients with poor soft-tissue condition and active infections 37 .…”
Section: Discussionmentioning
confidence: 99%
“…In the published publication [ 1 ], there were not added the affiliations for new added authors Tae-gon Kim, Jun Sung Moon and Seung Min Chung. The newly added affiliations appear here.…”
Section: Additional Affiliationsmentioning
confidence: 99%
“…Diabetes mellitus (DM) is a devastating disease that affects multiple organs, including the heart, kidneys, and nerves [ 1 , 2 ]. Diabetic foot is a common complication in approximately 6.3% of patients with DM [ 3 ].…”
Section: Introductionmentioning
confidence: 99%